A helynevek szerepe az alternatív ideologikus gondolkodásban II. Tudálékos helynév-etimológiák és új helynevek a Pilis-kultuszból [The role of place names in an alternative ideological mindset II. Pedantic place name etymologies and new place names from the Pilis Cult] - Imreh, Réka (Névtani Értesítő, 2015)
The paper is the second part of the study published in the previous issue of the same journal. The author describes the use of place names in a subculture that considers the Pilis Mountains the forgotten and destroyed scene of an ancient and glorious Hungarian past (conspiracy theory), and claims that the mountains are of spiritual importance. The author enumerates additional examples to illustrate the specific recontextualisation of place names in the Pilis Mountains. The alternative Pilis researchers explain the examined toponyms from a “Proto-Hungarian” and esoteric perspective; these place names are derived from prestigious languages and are placed into an appropriate associative network, and are then included in the alternative Pilis narrative, based mainly on their assumed etymology. The members of the subculture also act as name givers: they rename certain places, springs, etc. in the mountains; or give names to objects created by them. These newly given names might be printed on maps, which is the ultimate stage of the subculture symbolically occupying space through toponyms. The paper intends to give some interesting examples to the examination of place names adopting a social perspective.